2013
DOI: 10.1177/0894845313495512
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Career Calling and Perceived Overqualification on Work Outcomes for Primary and Secondary School Teachers

Abstract: While perceived overqualification (POQ) has received increased research attention in recent years, the identification of variables that moderate POQ-outcome relationships is critical to our understanding of how the construct affects career outcomes. This study, involving 170 full-time primary and secondary school educators in a suburban mid-Atlantic school system, found that POQ is negatively related to job satisfaction and affective commitment while positively related to turnover intentions and desire to turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 48 publications
4
63
1
8
Order By: Relevance
“…Teaching is a complex and challenging work that requires the highest standards of professional engagement (Lobene & Meade, 2013). Teachers are the key agents in today's knowledge society; however, their profession is often regarded as less attractive than many other professions .…”
Section: Introductionmentioning
confidence: 99%
“…Teaching is a complex and challenging work that requires the highest standards of professional engagement (Lobene & Meade, 2013). Teachers are the key agents in today's knowledge society; however, their profession is often regarded as less attractive than many other professions .…”
Section: Introductionmentioning
confidence: 99%
“…However, existing studies on the relationship between overqualification and task performance have reported conflicting results. Some studies have demonstrated that overqualification is associated with low task performance (e.g., Bolino & Feldman, ; Kristof‐Brown, Zimmerman, & Johnson, ), others have found that employees who feel overqualified perform better (e.g., Erdogan & Bauer, ; Fine & Nevo, ), and still others have found no direct relationship between overqualification and task performance (e.g., Lobene & Meade, ; Maynard, Rokitowski, & Bodolato, ). This indicates that there may be boundary conditions affecting the influence of perceived overqualification on task performance.…”
Section: Introductionmentioning
confidence: 99%
“…Examining this link is significant because, theoretically, overqualification represents a poor person–job fit (Maynard & Parfyonova, ), which has been suggested to be an important trigger of CWB (Luksyte, Spitzmueller, & Maynard, ). However, preliminary evidence linking overqualification with CWB is mixed at best (Lobene & Meade, ; Luksyte et al, ). Moreover, a theory‐based model that can incorporate multiple mediating paths and boundary conditions of the potential relationship between employee perceived overqualification and their misbehavior is yet to be developed.…”
mentioning
confidence: 99%